Effect of Heat Curing Temperatures on Fly Ash-Based Geopolymer Concrete - Muhammad, Norhasni; Baharom, Shahrizan; Amirah Mohamed Ghazali, Noor; Asiah Alias, Nor (International Journal of Engineering and Technology, 2019)
The geopolymer concrete (GC) is a cement replaced by aluminosilicate material combined with alkaline solution to produce strong binding property and replaced function of ordinary Portland cement. The purpose of this research was to determine the relationship between alkali solution concentrations (8 M, 10 M and 12 M), heat curing temperature and heat curing duration as the influencing parameters of concrete strengths. Geopolymer sample was prepared under different target heating temperatures which were room temperature and heat curing ranges of 60 Â°C to 100 Â°C for a duration curing period of 24 hours in the oven. Then the specimens were left in a room temperature until the testing day. The mechanical properties of geopolymer concrete were determined with the compressive test. The comparison was made with concrete control specimens that cured in ambient temperature. The results were determined from 7 days specimens after the curing process. The results show that the compressive strength of GCs under heat curing condition was developed quickly when there is an increase in temperature. It can be concluded that the temperature plays an important role in accelerating the GC strength increment compared to curing in ambient temperature.Â